PENGARUH PROMO TERHADAP MINAT BELI KONSUMEN (Study Pada Promosi, Cashback Dan Diskon Terhadap Minat Beli Konsumen Di Restaurant Mister Baso Di Mall CBD Cileduk) - Ardhya, Bella Nanda (Universitas Mercu Buana, 2019)
Abstract This research aims to find out the effects contained in various promo promos held by a restaurant where the promo promos are promotions, cashback and discounts all to attract consumers to buy mister baso. The total population used in this study is consumers who come to the mister baso retreat. The research method used in this research is quantitative research methods. The paradigm used is the positivistic paradigm. In this research paradigm, researchers want to find out how much the X variable is a price discount affecting the Y variable, namely buying interest. This research data is processed using Microsoft Excel and SPSS 23. Free variables in this study are Promotion (X1), Cashback (X2) and Discount (X3). The dependent variable in this study is buying interest (Y). the results of this study are that the variable promotions, cashback and discounts significantly influence buying interest. Free variable contribution (promotion, cashback and discount) to the dependent variable (buying interest) is 35.1%.